Implementation of PSAK 101 and 106 on The Financial Reports of BPRS HIK Parahyangan - Dewi, Irma Permata; Triguniawati, Nenden; Hanifa, Lia Hasna (CV. Strata Persada Academia, 2024)
PSAK 106 in the financial statements of Sharia Rural Credit Bank (BPRS) HIK Parahyangan. Indonesia's financial industry faces challenges due to technological advancements and evolving consumer behavior, requiring institutions like BPRS to adapt and comply with Sharia principles. PSAK 101 and 106 provide guidelines for Sharia-compliant financial statements and musyarakah transactions. This research evaluates BPRS HIK Parahyangan's compliance with these standards and their impact on financial reporting quality. A qualitative descriptive method is used, drawing on secondary data from financial reports, literature, and relevant documents, with thematic analysis applied. The study finds that the financial reports of BPRS HIK Parahyangan align with PSAK 101 and 106. PSAK 101 enhances reporting quality by standardizing Sharia transactions' presentation, ensuring transparency and accuracy for stakeholders. PSAK 106 supports investment and financing decisions by providing a reporting framework, fostering investor trust. By adhering to these standards, BPRS HIK Parahyangan demonstrates regulatory compliance and a commitment to transparent Sharia-based financial performance. This study benefits BPRS by improving reporting quality and contributes to Sharia accounting literature, offering insights for policymakers.